Geographical differentiation of mortality in the Republic of Moldova - PENINA, Olga (One Health & Risk Management, 2022)
Introduction. Life expectancy in Moldova after independence either fluctuated in the 1990s or stagnated in the early millennium, followed by moderate improvements since 2010. The objective of the study is to investigate the evolution of regional variations in life expectancy since independence in Moldova and to identify the main demographic components (causes of death and age groups) responsible for interregional mortality inequalities. Material and methods. Five-year average mortality rates by age and cause in the territorial profile were used for three periods: 1991-1995, 2002-2006 and 2012-2016. Abridged life tables and confidence intervals were computed. The difference in life expectancy between the two subpopulations was decomposed, according to Andreev’s method. Results. The gap in life expectancy between the best-performing and the worst-performing groups constitutes 6.0 years. Important progress has been made in the municipality of Chisinau and the northern districts of Briceni and Edinet concerning cardiovascular mortality. In 11 districts located mainly in the centre, the decline in infant mortality due to respiratory diseases was offset by the growth in adult mortality due to external causes and neoplasms. Conclusions. Regional disparities can be reduced through preventive measures targeting the key risk factors for cardiovascular disease, liver cirrhosis and external causes of death within the backward geographical area.